The comparison of the radiation load to the heart and the left anterior descending coronary artery for various modes of radiation treatment of the breast cancer patients - A. V. Bondarenko; L. I. Korytova; E. A. Maslyukova; O. V. Korytov; E. M. Muravnik (ABV-press, 2016)
Objective: the comparison of the radiation load to the organs at risk for three modes of radiation treatment of the breast cancer patients.Materials and methods. The research includes the dosimetric radiation treatment plans for the 20 breast cancer patients with the left-side localization. They all underwent a computed tomography (CT) scan in standard supine position in free-breathing (FB), supine position with active breathing control (ABC) device in deep inspiratory breath hold, and prone position in free-breathing (PP). Three-dimensional treatment plans were made for all 3 CTs. The dose valuations for 3D-planning were carried out for three CT-series. For each mode of radiation the doze-volume parameters of organs at risk were estimated: heart volume exposed to more than 25 Gy (V25 heart), mean dose (Dmean) to the heart and left anterior descending coronary artery (LAD).Results. For all cases the contoured heart volume varied from 477-1056 cm3, with medium volume 769 cm3. The best marks such as V25 heart, Dmean heart and Dmean LAD, were achieved with on supine position with ABC method (4.25 %, 3.13 Gy, 1.3 Gy, respectively) in comparison with FB (9.49 %, 4.96 Gy, 1.95 Gy, respectively) and PP (12.8 %, 9.06 Gy, 24.18 Gy, respectively) (V25 heart: p = 0.00153; Dmean heart: p = 0,000; Dmean LAD: p = 0.00088), when both the breast and the axillary nodes were included in the volume. The advantage of the dosimetric indexes for FB and ABC did not change while axillary and supraclavicular nodes were added to the radiation volume ABC (V25 heart 3.49 %, Dmean heart 3.07 Gy, Dmean LAD 13.8 Gy) in comparison with FB methods (V25 heart 7.91 %, Dmean heart 4.99 Gy, Dmean LAD 19.89 Gy) (V25 heart: p = 0.00205; Dmean heart: p = 0.004; Dmean LAD: p = 0.03).Conclusion. Radiation treatment of the breast cancer patients in the position with ABC contributed to the statistically significant reduction of the dosimetric parameters: V25 heart, Dmean heart and Dmean LAD.